If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + 2q = 10 Solving p + 2q = 10 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2q' to each side of the equation. p + 2q + -2q = 10 + -2q Combine like terms: 2q + -2q = 0 p + 0 = 10 + -2q p = 10 + -2q Simplifying p = 10 + -2q
| -5(f+7)=3(3f+-1) | | -4(r+3)=-70 | | 3x+5+3x+5+x+x=66 | | 2x-6x+8x-9x= | | (2x+3)(x+5)= | | m^2-28m+25=0 | | 6k-k=27-4 | | 43(x-172)=86 | | 5x^2+34+24=0 | | w^2+17w+16=0 | | 3x+5+x=66 | | 0.20(x+10)+1.40x=66 | | 0.5(8w-6)=17 | | 5(-1.2)-y=4 | | 8w+3=6 | | 3*l=5 | | 4x-6+x=54 | | 5y+1+3y=-5 | | 4=16t-16t^2 | | 9-33=-4z | | -3x-4z=17 | | 5z^2-3x-2=0 | | 3(w-2)=6 | | 2x+3+x=54 | | w-3w=32 | | 2x+3=54 | | 0=-3x^2+2x+5 | | 4x-2(x+5)=-(2x+15) | | 4x-2(x+5)=-(2v+15) | | 3a+b=10 | | 3a-2b=-2 | | .75-9p=.60 |